College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Section P.6 - Factoring - P.6 Exercises - Page 43: 104



Work Step by Step

$(x+1)^{3}x-2(x+1)^{2}x^{2}+x^{3}(x+1)=x(x+1)[(x+1)^{2}-2(x+1)x+x^{2}]=x(x+1)[(x+1)-x]^{2}=x(x+1)[x-x+1]^{2} =x(x+1)(1)^{2}=x(x+1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.